2021
DOI: 10.1161/jaha.120.018090
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Ventricular Arrhythmias and 1‐Year Predictors of Mortality in Patients Treated With Implantable Cardioverter‐Defibrillator Undergoing Generator Replacement

Abstract: Background When implantable cardioverter defibrillator (ICD) battery is depleted most patients undergo generator replacement (GR) even in the absence of persistent ICD indication. The aim of this study was to assess the incidence of ventricular arrhythmias and the overall prognosis of patients with and without persistent ICD indication undergoing GR. Predictors of 1‐year mortality were also analyzed. Methods and Results Patients with stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…In the SCD‐HeFT trial, the HF death rate among ICD patients after an appropriate shock was 43%, with a median time from shock to death of 168 days, which was similar to our result 4 . However, recent studies reported that among ICD patients who received generator exchange, advanced age and non‐cardiac comorbidities were associated with all‐cause mortality after generator exchange (mean time from initial implantation of 5 years), suggesting that the mode of death transitions from cardiac causes to non‐cardiac causes over time 9,10 . Interestingly, our data showed that in the late group, HF death was still a major cause of death after an appropriate shock.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In the SCD‐HeFT trial, the HF death rate among ICD patients after an appropriate shock was 43%, with a median time from shock to death of 168 days, which was similar to our result 4 . However, recent studies reported that among ICD patients who received generator exchange, advanced age and non‐cardiac comorbidities were associated with all‐cause mortality after generator exchange (mean time from initial implantation of 5 years), suggesting that the mode of death transitions from cardiac causes to non‐cardiac causes over time 9,10 . Interestingly, our data showed that in the late group, HF death was still a major cause of death after an appropriate shock.…”
Section: Discussionsupporting
confidence: 86%
“…suggesting that the mode of death transitions from cardiac causes to non-cardiac causes over time. 9,10 Interestingly, our data showed that in the late group, HF death was still a major cause of death after an appropriate shock. There are several explanations for this result.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…A total of 31,640 patients from 20 studies (14 retrospective and 6 prospective registries) were included in our meta-analysis (Figure 1) with a mean ± standard deviation age of 65.6 ± 4.7 years (mean age range, 57-76 years) and follow-up period of 3.1 ± 1.5 years. 2,6,10,11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The critical appraisal performed using the Newcastle-Ottawa scale revealed that the quality of studies was good (Table S1).…”
Section: Resultsmentioning
confidence: 99%